Japan : - Haasch, Günther (Colloquium Verlag, 1973)
Japan is located in East Asia and Tokyo is the capital of the country as it is one of the largest cities of Japan. According to the Chinese records, there held various battles between the small cities of Japan and finally, the war concluded and a famous queen ruled the country for several years.